Treatment with 24 h–delayed normo- and hyperbaric oxygenation in severe sepsis induced by cecal ligation and puncture in rats. Issue 1 (December 2017) - Bærnthsen, Nina; Hansen, Marco; Wahl, Anna; Simonsen, Ulf; Hyldegaard, Ole
Abstract Background Septic shock remains a leading cause of death worldwide. Hyperbaric oxygen treatment (HBO2 ) has been shown to alter the inflammatory response during sepsis and to reduce mortality. A therapeutic window of HBO2 treatment has been demonstrated experimentally, but optimal timing remains uncertain. We investigated the effects of 24 h delayed normobaric oxygen (NBO2 ) and HBO2 treatment on the endogenous production of the inflammatory markers interleukin (IL)-6, tumor necrosis factor (TNF)-α and IL-10, and on mortality in rats with cecal ligation and puncture (CLP) induced sepsis. Method Fifty-five male Sprague-Dawley rats underwent CLP and were randomized to the following groups: 1) HBO2 2.5 bar absolute pressure (pabs ); 2) NBO2 1.0 bar pabs ; 3) Control (no-treatment), and they were individually monitored for 72 h with intermittent blood sampling. Results IL-6, TNF-α, and IL-10 were increased 24 h after the procedure, and IL-6 was significantly higher in non-survivors than in survivors. The level of IL-10 was significantly higher at hour 48 in the HBO2 group compared to control (p = 0.01), but this was not the case at other time points. No other significant differences in cytokine levels were found for any group comparisons. Delayed NBO2 and HBO2 treatment failed to change the mortality in the animals. Conclusion High levels of IL-6 in non-surviving animals with sepsis suggest that IL-6 is a potential biomarker. We found a significantly higher concentration of IL-10 in the HBO2 group at hour 48 vs. control animals. However, 24 h–delayed treatment with HBO2 did not change the levels of pro-inflammatory cytokines and survival, suggesting that earlier intervention may be required to obtain an anti-inflammatory effect.